Bronchiectasis and the risk of cardiovascular disease: a population-based study. Issue 2 (29th August 2016) - Navaratnam, Vidya; Millett, Elizabeth R C; Hurst, John R; Thomas, Sara L; Smeeth, Liam; Hubbard, Richard B; Brown, Jeremy; Quint, Jennifer K
Abstract : Background: There are limited data on the burden of cardiovascular comorbidities in people with bronchiectasis. Our cross-sectional study estimates the burden of pre-existing diagnoses of coronary heart disease (CHD) and stroke in people with bronchiectasis compared with the general population. The historical cohort study investigates if individuals with bronchiectasis are at increased risk of incident CHD and stroke events. Methods: We used primary care electronic records from the Clinical Practice Research Datalink. The cross-sectional study used logistic regression to quantify the association between bronchiectasis and recorded diagnoses of CHD or stroke. Cox regression was used to investigate if people with bronchiectasis experienced increased incident CHD and strokes compared with the general population, adjusting for age, sex, smoking habit and other risk factors for cardiovascular disease. Results: Pre-existing diagnoses of CHD (OR 1.33, 95% CI 1.25 to 1.41) and stroke (OR 1.92, 95% CI 1.85 to 2.01) were higher in people with bronchiectasis compared with those without bronchiectasis, after adjusting for age, sex, smoking and risk factors for cardiovascular disease. The rate of first CHD and stroke were also higher in people with bronchiectasis (HR for CHD 1.44 (95% CI 1.27 to 1.63) and HR for stroke 1.71 (95% CI 1.54 to 1.90)). Conclusion: The risk of CHD and stroke are higher among people with bronchiectasis compared with the general population. An increased awareness of these cardiovascular comorbidities in this population is needed to provide a more integrated approach to the care of these patients.